Social prescribing for older adults in mainland Portugal: Perceptions and future prospects - Costa, A. S.; Henriques, J.; Alarcão, V.; Madeira, T.; Virgolino, A.; Henriques, A.; Feteira-Santos, R.; Polley, M.; Arriaga, M.; Nogueira, P. (Preventive Medicine Reports, 2024)
Background In order to address health inequalities, which have been exacerbated by the COVID-19 pandemic, and promote older adults’ quality of life, it is necessary to explore non-medical approaches such as social prescribing. Social prescribing is a person-centered approach that allows health professionals to refer patients to services provided by the social and community sectors. This study aimed to explore older adults' perceptions of social prescribing in mainland Portugal and to identify factors associated with these perceptions, providing insights for future implementation strategies. Methods A cross-sectional study was conducted with 613 older adults aged 65 to 93. Participants' sociodemographic, economic, and health characteristics were assessed, along with their perceptions of social prescribing’s benefits and activity interest. Results Over 75% of respondents agreed that social prescribing would benefit the health system and their community. Most participants (87.7% and 89.7%, respectively) thought that activities like personal protection and development activities and cultural enrichment would be particularly relevant to them. Factors such as marital status, education, health status, and pain/discomfort levels influenced the perceived relevance of these activities. Conclusion This study reveals that older adults in mainland Portugal are open to social prescribing and suggests that tailored interventions considering individual preferences and characteristics can lead to more effective implementation and equal access to social prescribing. Further research and policy efforts should focus on integrating social prescribing into the healthcare system to support healthy aging in Portugal.